A Phase III, Randomized, Double-Blind, Placebo-Controlled Trial of Pegfilgrastim in Patients Receiving First-Line FOLFOX/Bevacizumab or FOLFIRI/Bevacizumab for Locally Advanced or Metastatic Colorectal Cancer: Final Results of the Pegfilgrastim and Anti-VEGF Evaluation Study (PAVES) - Pinter, Tamás; Klippel, Zandra; Cesas, Alvydas; Croitoru, Adina; Decaestecker, Jochen; Gibbs, Peter; Hotko, Yevhen; Jassem, Jacek; Kurteva, Galina; Novotny, Jan; O'Reilly, Seamus; Salek, Tomas; et al. (Clinical colorectal cancer, 2017)
BACKGROUND: Pegfilgrastim's role in reducing the risk of febrile neutropenia (FN) in patients with colorectal cancer (CRC) receiving chemotherapy plus bevacizumab was not previously evaluated in a prospective study. The present phase III, double-blind trial evaluated the efficacy of pegfilgrastim versus placebo in reducing the incidence of grade 3/4 FN in patients with advanced CRC receiving bevacizumab combined with first-line chemotherapy (FOLFOX [leucovorin, 5-fluorouracil, oxaliplatin] or FOLFIRI [leucovorin, 5-fluorouracil, irinotecan]). PATIENTS AND METHODS: Patients aged ≥ 18 years with locally advanced or metastatic CRC were randomized 1:1 to placebo or 6 mg of pegfilgrastim ∼24 hours after receiving chemotherapy plus bevacizumab every 14 days. The study treatment period included 4 cycles, but patients could continue treatment for ≤ 60 months. The primary endpoint was incidence of grade 3/4 FN in the first 4 cycles. The secondary endpoints included the objective response rate (ORR), overall survival, and progression-free survival, analyzed at the end of the long-term follow-up period. RESULTS: A total of 845 patients were randomized from November 2009 to January 2012 (422, pegfilgrastim; 423, placebo). Pegfilgrastim significantly reduced the incidence of grade 3/4 FN in the first 4 treatment cycles (pegfilgrastim, 2.4%; 95% confidence interval [CI], 1.1%-4.3%; placebo, 5.7%; 95% CI, 3.7%-8.3%; odds ratio [OR], 0.41; P = .014). No significant differences were observed between the 2 arms in ORR (OR, 1.15; P = .330), overall survival (hazard ratio, 0.94; P = .440), and progression-free survival (hazard ratio, 0.93; P = .300). CONCLUSION: Pegfilgrastim reduced the FN incidence in patients with advanced CRC receiving chemotherapy and bevacizumab. Administration of pegfilgrastim was tolerable and did not negatively affect the tumor response or survival in this patient population.
Keywords: senioři nad 80 let; bevacizumab; Bevacizumab; přežití bez známek nemoci; Filgrastim; Humans; Vascular Endothelial Growth Factor A; Febrile Neutropenia; kamptothecin; lidé; prospektivní studie; Colorectal Neoplasms; organoplatinové sloučeniny; proporcionální rizikové modely; Aged, 80 and over; leukovorin; Prospective Studies; Fluorouracil; incidence; fluoruracil; filgrastim; mladý dospělý; Proportional Hazards Models; Female; Double-Blind Method; Incidence; protokoly protinádorové kombinované chemoterapie; lidé středního věku; Neoplasm Metastasis; Polyethylene Glycols; Male; Survival Rate; polyethylenglykoly; následné studie; Follow-Up Studies; febrilní neutropenie; Camptothecin; Leucovorin; Adult; dvojitá slepá metoda; dospělí; metastázy nádorů; Organoplatinum Compounds; senioři; Aged; kolorektální nádory; míra přežití; Disease-Free Survival; ženské pohlaví; mužské pohlaví; Middle Aged; vaskulární endoteliální růstový faktor A; Antineoplastic Combined Chemotherapy Protocols; Young Adult